Cadmium decreases human gingival fibroblast viability and induces pro-inflammatory response associated with Akt and MAPK pathway activation - Tipparat Parakaw; Sirada Srihirun; Nathawut Sibmooh; Nisarat Ruangsawasdi; Phisit Khemawoot; Pornpun Vivithanaporn (Frontiers in Toxicology)
Smoking and particulate matter 2.5 (PM2.5) expose millions to cadmium (Cd), a toxic heavy metal linked to pro-inflammatory responses, oxidative stress, and disease pathogenesis. In the oral cavity, chronic Cd exposure contributes to the progression of periodontal diseases and oral cancers. However, the direct effect of Cd on oral tissues and the underlying mechanisms remains unclear. This study explored the impact of environmentally relevant concentrations of Cd on human gingival fibroblasts (HGFs) by evaluating cell viability, pro-inflammatory cytokine secretion (IL-6 and IL-8), COX-2 expression, and the activation of key signaling pathways: Akt, ERK1/2, and JNK. Cd exposure significantly reduced HGF viability, elevated IL-6 and IL-8 secretion, and upregulated COX-2 expression. These effects were attenuated by inhibitors targeting Akt, ERK1/2, and JNK pathways. By integrating cytokine profiling, COX-2 expression, and inhibitor-based pathway analysis, our study provides mechanistic insights into how low-level Cd exposure triggers early inflammatory responses in gingival fibroblasts. Our findings reveal that Cd exerts pro-inflammatory and cytotoxic effects on HGFs, which may play a role as one of the factors in the pathogenesis of smoking-related oral diseases. Targeting Akt, ERK1/2, and JNK signaling pathways could offer therapeutic strategies to attenuate Cd-induced oral pro-inflammatory responses and tissue damage.